iGOT Karmayogi Platform: A Digital Content Framework for Sharing Knowledge about Civil Services - Dr. H M Naveen (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The iGOT Karmayogi would need to cater to the diverse learning needs, preferences, and interests of a variety of 21st century learners, and will be sufficiently exhaustive to cater to the learning needs of the civil services- both for their professional development and personal learning interests- instilling in them the attitudes, skills and knowledge to enable a more sustainable and just society for all according to the guidelines. This Content Framework is a recommendations document that provides guidance and standards for the development of online learning products for iGOT Karmayogi as per the Content Framework document. It is a guide for the learning community including CTIs, ATIs, content providers/external vendors, reviewers, learning managers and staff working or interested in creating online learning programmes as per the Content Framework guidelines. Thus, keeping this in mind the present article has been drafted to enlighten the readers about the Types of content that will be onboarded on the platform; Content lifecycle; Content Framework; WTDET Model; Benefits of the proposed Framework; Human-Centered Design Process; Diversity and Inclusion; Sustainable Development (SD); Content Appropriateness & Copyright, and Originality. This Content Framework can be used to guide the development and implementations and review the online Competency-Based Products (CBPs); integrate cultural diversity and gender perspective in all areas of online learning programmes; and produce accessible digital content that all learners, regardless of disabilities, are able to understand and interact with it. Thus, the Content Framework on iGOT Platform is based on the instructional design methods for developing and delivering learning programmes that seeks to change behaviour and improve performance. Thus, the learner-centered, action-oriented and transformative content shall be onboard on the iGOT Platform.